Franco Núñez,Amy Nohely(2023)DESARROLLO DE BARRITAS DE CEREALES CON VARIEDADES DE QUINUA (Chenopodium quinoa) EMPLEANDO AGLUTINANTES NATURALES.Quevedo.UTEQ.110p. - Franco Núñez , Amy Nohely (2023)
The purpose of this research was to develop cereal bars with varieties of quinoa: white, red, and black (Chenopodium quinoa), using two types of natural binders, bee honey, and cocoa mucilage. A completely randomized AxB design was applied, resulting in six treatments and three replicates. Tukey's multiple range test (p ≤0.05) was used to determine the differences between treatments. Physicochemical variables were analyzed (moisture, ash, pH, acidity, ethereal extract, total nitrogen, crude fiber, carbohydrates, and energy-Kcal); where treatments T1, T2, T4 stood out for their protein, fat, and energy content, however, for carbohydrates T5 stood out; while for fiber and ash, no statistical differences were obtained, remaining with values around 3.30% and 1.60% respectively in all samples. On the other hand, the treatments containing cocoa mucilage obtained lower pH values and higher acidity, being statistically different from those that included bee honey. The non-parametric Kruskall-Wallis test was applied for the sensory analysis, which resulted in T2 (white quinoa + cocoa mucilage) as the best treatment, to which the analysis of total polyphenol content of 0.20 mg AG/100 g and a microbiological analysis were performed, which obtained values of E. coli < 10 cfu/g, molds and yeasts < 10 cfu/g, which allow us to conclude that the product complies with NTE INEN 2595:2011 "Granola - Requirements"; obtaining a selling price of $ 0.77 ctvs. for each 55 g cereal bar and profitability of 15%.